On the morphology of Plectrohyla chryses (Anura: Hylidae; Hylini), with comments on some controversial characters, phylogenetic relationships, and diagnosis of this species (2016)
We describe the tadpole and juvenile of Plectrohyla chryses and conduct an analysis of skin thickness and a general phylogenetic analysis of the Hylini to determine the phylogenetic position of P. chryses. We found that P. chryses has thin skin and that is part of the P. bistincta group. We also found that adult P. chryses have an axillary membrane and a thoracic fold, but that the rostral keel is absent. We conclude that only the character “skin thickness” is useful for the diagnosis of P. chryses, and we propose a new diagnosis for this species.